Elevated serum uric acid is associated with cognitive impairment in acute minor ischemic stroke patients - Lei Xu; Qing-rong Ouyang; Qin Xiong; Lu-wen Huang; Ming Yu (Heliyon, 2023)
Background: Acute minor ischemic stroke (AMIS) has been proven to be strongly associated with post-stroke cognitive impairment (PSCI). Few studies have reported that uric acid (UA) levels are linked to PSCI in patients with AMIS, and those results are debatable. We investigated the relationship between serum UA levels and cognitive impairment in patients with AMIS. Methods: A total of 318 patients who were diagnosed with AMIS were recruited from Suining Central Hospital. Fasting serum samples were collected the day after admission for UA measurement. Cognitive function was evaluated at admission and 3 months after stroke using the Montreal Cognitive Assessment (MoCA). The relationship between UA and PSCI was examined using a multivariate binary logistic regression model. The optimal cut-off point for UA levels to predict PSCI was determined using the receiver operating characteristic (ROC) curve. Results: A total of 197 (61.9 %) of the 318 participants in this study exhibited cognitive impairment at 3 months. Serum UA was strongly linked with PSCI after adjusting for confounding factors (OR = 1.82, 95 % CI: 1.56 to 2.11, P < 0.0001). The ROC curve revealed a cut-off of 363.58 μmol/L serum UA, and the predicted sensitivity and specificity for PSCI were 67.5 % and 83.5 %, respectively. Subgroup analysis showed that confounding factors had no impact on the association between serum UA and PSCI risk. Conclusions: Higher baseline serum UA levels might be an independent risk factor for cognitive impairment in AMIS patients. Serum UA levels above 363.58 μmol/L may have clinical implications in predicting PSCI.